FAKTOR-FAKTOR YANG MEMPENGARUHI SELF EFFICACY PADA PASIEN PASCA STROKE DI WILAYAH KERJA UPT PUSKESMAS TERMINAL KOTA BANJARMASIN - Emellia, Emellia; Gaghauna, Eirene E.M; Irawan, Angga (STIKES Suaka Insan, 2023)
Post-stroke dysfunction can affect the psychological and social aspects of patients, such as feelings of inferiority, disadvantage, wanting to recover reduced abilities, sadness, anxiety, and hopelessness. These symptoms reflect low self-efficacy. This study aims to determine what factors affect self-efficacy in post-stroke patients in the Banjarmasin City Terminal Health Centre Work Area. The population in this study was 60 people and the sample used was 52 people, who were taken using the purposive sampling technique. Univariate and bivariate data analysis with Kolmogorov-Smirnov and cell merging. The results of this study indicate that there were significant differences between gender, age, education, and family support for self-efficacy in post-stroke patients. Statistical analysis showed significant differences between gender (p=0.009), age (p=0.002), education (p=0.000), and family support (p=0.003) on self-efficacy in post-stroke patients. Patients who suffer from stroke are expected to maintain good self-efficacy in an effort to maximize care and treatment. Keywords: Age, Education, Gender, Family Support, Self Efficacy, Stroke